Based on Anti-windup PI of brushless Dc motor control system design - Miao JingLi; Huang XiaoGuang; Yuan Xiangmeng (Institute of Advanced Engineering and Science, 2014)
In this paper, on the simulation model of brushless DC motor, for brushless DC motor speed controller adopts Anti-windup PI saturated controller. According to the output of the controller is saturated, integral output feedback to the input, by the integral state control. It is that integral controller using the conditions with the computing strategy of control algorithm, so ensure the controller when a saturated. As soon as possible from the saturated zone, reached the overshoot volume is reduced. The simulationexperimental results show that the control method can effectively inhibit integral saturation and implement system response speed. It is good that the system has good robustness and steady-state performance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3934